PEMENUHAN NAFKAH PADA KELUARGA AKTIVIS JAMAAH TABLIGH DI KOTA AMUNTAI KALIMANTAN SELATAN - Laili, Afrohatul; Nida, Khairun; Ulum, Wildanul (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
Responsibilities as a family leader, both related to fulfilling physical and spiritual livelihoods, have the ultimate goal of benefiting the family both in this world and in the hereafter. Among Jamaah Tabligh activists, there are things they cannot leave behind, so heads of households have to leave their family members for a short period of time. Therefore, a Jamaah Tabligh activist who is performing Khuruj must still ensure that his and his family's livelihood is met in a reasonable and legal manner. This research uses qualitative research methods with a descriptive approach. This research is based on research objects through observation, interviews and documentation conducted with the Jamaah Tabligh who are married in the Hulu Sungai Utara Regency area.  Researchers will use analytical methods, namely after the data is collected, it is clarified according to the problem being discussed and the contents analyzed to draw conclusions. The results of this research indicate that all the living needs of the wife and children are adequately met because each member always takes into account all the needs of the family members who will be left behind by deliberating on all necessary needs before Khuruj's departure. Apart from that, the activists not only provide understanding, but this understanding is accompanied by several da'wah activities which also involve wives and other family members, such as masturah activities which they regularly hold and several additional routine studies which are also specifically for female members. This study has an impact on their generosity in accepting all situations in their household.